2018
DOI: 10.1187/cbe.17-11-0239
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Issues in Group Learning in Undergraduate Science Classrooms: A Perspective from Student Engagement

Abstract: As the use of collaborative-learning methods such as group work in science, technology, engineering, and mathematics classes has grown, so has the research into factors impacting effectiveness, the kinds of learning engendered, and demographic differences in student response. Generalizing across the range of this research is complicated by the diversity of group-learning approaches used. In this overview, I discuss theories of how group-work formats support or hinder learning based on the ICAP (interactive, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 65 publications
(76 reference statements)
2
37
0
1
Order By: Relevance
“…In general, a face‐to‐face interactive educational session with a group were most often identified as preferable. As pointed out by earlier studies (Graham, ; Hodges, ), the perceived benefits of a face‐face interactive educational session with a group are the ability to group‐think, share ideas, and learn from other members while receiving prompt feedback. This approach also supports the main purpose of continual professional development, which is to update nurses’ knowledge and skills for enhanced and improved patient care (Filipe, Silva, Stulting, & Golnik, ).…”
Section: Discussionmentioning
confidence: 98%
“…In general, a face‐to‐face interactive educational session with a group were most often identified as preferable. As pointed out by earlier studies (Graham, ; Hodges, ), the perceived benefits of a face‐face interactive educational session with a group are the ability to group‐think, share ideas, and learn from other members while receiving prompt feedback. This approach also supports the main purpose of continual professional development, which is to update nurses’ knowledge and skills for enhanced and improved patient care (Filipe, Silva, Stulting, & Golnik, ).…”
Section: Discussionmentioning
confidence: 98%
“…Instructors often struggle with the question of whether student learning is best promoted by using permanent teams or by re-forming teams periodically. Although evidence is scant on this issue (Hodges, 2018), it is possible that the more time students spend together, the more they are able to, or practice, decentering behaviors, in which they take on the perspective of another individual or context besides their own (Moon et al, 2017). In addition, a study in a peer instruction classroom found that students became more expert-like in their thinking if groups were permanent (Zhang et al, 2017).…”
Section: Conclusion and Recommendations For Practicementioning
confidence: 99%
“…All groups, especially Group 4, had difficulties with time management which is not surprising because time issues are a reported problem in courses (Hodges 2018). To address this issue in advance the course had five milestones for the groups to deliver first results.…”
Section: Situation Three: Groups Dealt With Time Management Differentlymentioning
confidence: 99%